Tests to evaluate public health disease reporting systems in local public health agencies - Dausey, David J. (Technical report (Rand Corporation), 2005)
Despite the importance of public health disease reporting systems in an age of increasing globalization, few standardized tools have been developed to help public health agencies evaluate their effectiveness. This operations manual provides public health agencies with a set of standardized proficiency tests to aid in the development of regular and consistent strategies for testing the ability of public health disease reporting systems to receive and respond to case reports 24 hours a day, seven days a week. The manual serves as a guidebook for planning a test and as a training and reference manual for individuals conducting a test; provides tools and templates necessary to conduct the tests; and provides benchmarks to evaluate testing performance. The goal of these tests is to assess whether a local public health agency has sufficient proficiency to respond to public health disease reports as outlined by the Centers for Disease Control and Prevention. The tests are intended to be used over time to regularly monitor and improve performance of public health disease reporting systems.